The origins of the Second World War reconsidered : A. J. P. Taylor and the historians - Martel, Gordon 1946- Hrsg (Routledge, 1999)
The revisionist as moralist: A.J.P. Taylor and the lessons of European history / Gordon Martel -- 1918 and after: the postwar era / Sally Marks -- The end of Versailles / Stephen A. Schuker -- Mussolini and the myth of Rome / Alan Cassels -- A.J.P. Taylor and the problem with France / Robert J. Young -- Misjudging Hitler: A.J.P. Taylor and the Third Reich / Richard Overy -- Appeasement / Paul Kennedy and Talbot Imlay -- Debating the role of Russia in the origins of the Second World War / Teddy J. Uldricks -- Japan at war: history-writing on the crisis of the 1930s / Louise Young -- More than meets the eye: the Ethiopian War and the origins of the Second World War / Brian R. Sullivan -- The Spanish Civil War and the origins of the Second World War / Mary Habeck -- The phantom crisis: Danzig, 1939 / Sean Greenwood